2015
DOI: 10.1504/ijmef.2015.072342
|View full text |Cite
|
Sign up to set email alerts
|

Exchange rate pass-through to domestic prices in Tunisia: a short- and long-run analysis

Abstract: This study analyzes the impact of the exchange rate fluctuations in the short and long-runs in Tunisia under a pure commitment policy through two channels. The first is the Structural Vector Autoregression used to analyze the short run effects of the exchange rate on the industrial production index and on the consumer and import price indexes. The second is the Vector Error Correction Model used to examine the long run dynamic effects of the exchange rate upon the same variables relying on Tunisian monthly dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…From 1990 to 2018, global oil prices experienced significant volatility, including notable price increases during this period, which affected the prices of not only energy-related products but also other goods and services that rely on oil as an input or transportation. This pass-through effect led to a broad-based increase in prices across the economy, resulting in higher inflation (as demonstrated by Jbir and Zouari-Ghorbel, 2009;Guenichi and Benamou, 2010;Helali and Kalai, 2015;El-Hamiani, 2018). A relative decrease in the impact of oil prices on inflation from 2019 to 2022 can be attributed to several factors as suggested by Gritli (2021) and El-Hamiani et al (2020): monetary policy measures; government subsidies; demand-supply dynamics; and structural reforms.…”
Section: Resultsmentioning
confidence: 97%
“…From 1990 to 2018, global oil prices experienced significant volatility, including notable price increases during this period, which affected the prices of not only energy-related products but also other goods and services that rely on oil as an input or transportation. This pass-through effect led to a broad-based increase in prices across the economy, resulting in higher inflation (as demonstrated by Jbir and Zouari-Ghorbel, 2009;Guenichi and Benamou, 2010;Helali and Kalai, 2015;El-Hamiani, 2018). A relative decrease in the impact of oil prices on inflation from 2019 to 2022 can be attributed to several factors as suggested by Gritli (2021) and El-Hamiani et al (2020): monetary policy measures; government subsidies; demand-supply dynamics; and structural reforms.…”
Section: Resultsmentioning
confidence: 97%
“…Our results show that the exchange has an indirect and negative effect on economic growth and this direct effect is transmitted to prices in short and long-run. In other words, the short-and long-term effects of the exchange rate on economic growth and prices have shown that through import prices, the strong effect of the transmission of the exchange rate is reflected in the first step on domestic prices, that is to say that the depreciation of the domestic currency generates an increase in the price level which subsequently influences economic growth in Tunisia (Helali & Kalai 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Then, since the January 2011 revolution, the fragile economic situation and high inflation rates led to a weak mobilization of deposits and several Tunisian banks found themselves in a situation of insufficient liquidity and increasing dependence on direct refinancing by the Central Bank of Tunisia (IMF National Report, 2015;Helali & Kalai, 2015;Helali, 2020;Helali et al, 2021) which prompted the CBT to decrease its nominal rate by 100 basis points, from 4.5% to 3.5% with the reduction of the required reserve ratio of commercial banks from 12% to 2% and giving 2.6 billion dollars to commercial banks to boost liquidity (Matta et al, 2019). The aim was to reduce the financial burden on companies, especially those affected by the effects of the political crisis, and to increase the liquidity of financial intermediation.…”
Section: Introductionmentioning
confidence: 99%